2018
DOI: 10.2174/2212798409666171129173802
|View full text |Cite
|
Sign up to set email alerts
|

Edible Mushrooms from Niger Delta, Nigeria with Heavy Metal Levels of Public Health Concern: A Human Health Risk Assessment

Abstract: Nickel showed the highest carcinogenic risk with values of 4.83E-04 - 1.43E-01, 5.31E-04 - 1.00E-01 and 1.20E-03 - 2.29E-01 for adults, adolescents and children respectively. About 80% of TCR ranged from x10-1 - x10-3. Consumption of mushroom in Niger delta-Nigeria may pose significant health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A study by Igbiri et al [ 44 ] investigated the THQ and HR of PTE in edible mushroom species in the Niger Delta, Nigeria. They observed that the maximum HR values were identified for Ni heavy metal, indicating serious health risks for the consumers.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Igbiri et al [ 44 ] investigated the THQ and HR of PTE in edible mushroom species in the Niger Delta, Nigeria. They observed that the maximum HR values were identified for Ni heavy metal, indicating serious health risks for the consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, more research efforts are required to fully understand the mechanism and metabolic pathways of mushroom bioactives for their pharmacological activities. Both wild and cultivated mushrooms consist of metals and trace elements like cadmium (Cd), selenium (Se), chromium (Cr), lead (Pb), arsenic (As), mercury (Hg), zinc (Zn), and nickel (Ni) among which some elements are toxic to humans if consumed daily [ 154–156 ]. Mleczek et al, in a very recent study, reported different elements present in four wild-type mushrooms ( Boletus edulis, Imleria badia, Leccinum scabrum , and Macrolepiota procera ) and concluded that over intake of mushrooms may result in health risks to humans [ 157 ].…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…For example, symptoms of Zn deficiency include growth retardation, hair loss, diarrhea, eye and skin lesions, loss of appetite, and delayed wound healing [ 17 ]. The ability of wild mushrooms to accumulate metallic elements and metalloids in their tissues is well documented by other authors [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], showing that the concentrations of these contaminants in the wild-growing species are considerably greater than those in the soil where they grew [ 28 ]. The mechanism that enables mushrooms to accumulate metallic elements and metalloids could be explained via the network of hyphae located in the upper soil horizon [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 72%